Postpartum haemorrhage in high-resource settings: variations in clinical management and future research directions based on a comparative study of national guidelines - de Vries, PLM; Deneux-Tharaux, C; Baud, D; Chen, K; Donati, S; Goffinet, F; Knight, M; McLintock, C; D'Souza, R; Sueters, M; van den Akker, T (Wiley, 2023)
Objective To compare guidelines from eight high-income countries on prevention and management of postpartum haemorrhage (PPH), with a particular focus on severe PPH. Design Comparative study. Setting High-resource countries. Population Women with PPH. Methods Systematic comparison of guidance on PPH from eight high-income countries. Main outcome measures Definition of PPH, prophylactic management, measurement of blood loss, initial PPH-management, second-line uterotonics, non-pharmacological management, resuscitation/transfusion management, organisation of care, quality/methodological rigour. Conclusions Our study highlights areas where strong evidence is lacking. There is need for a universal definition of (severe) PPH. Consensus is required on how and when to quantify blood loss to identify PPH promptly. Future research may focus on timing and sequence of second-line uterotonics and non-pharmacological interventions and how these impact maternal outcome. Until more data are available, different transfusion strategies will be applied. The use of clear transfusion-protocols are nonetheless recommended to reduce delays in initiation. There is a need for a collaborative effort to develop standardised, evidence-based PPH guidelines. Results Definitions of (severe) PPH varied as to the applied cut-off of blood loss and incorporation of clinical parameters. Dose and mode of administration of prophylactic uterotonics and methods of blood loss measurement were heterogeneous. Recommendations on second-line uterotonics differed as to type and dose. Obstetric management diverged particularly regarding procedures for uterine atony. Recommendations on transfusion approaches varied with different thresholds for blood transfusion and supplementation of haemostatic agents. Quality of guidelines varied considerably.